2018
DOI: 10.1111/jgs.15573
|View full text |Cite
|
Sign up to set email alerts
|

‘Til Death Do Us Part: End‐of‐Life Experiences of Married Couples in a Nationally Representative Survey

Abstract: Background/Objectives: Among married couples, the death of one’s spouse can influence perceptions of health services available at the end-of-life (EOL). However, it is unknown if one spouse’s EOL experience is associated with the widowed spouse’s uptake of health services or advance care planning (ACP). We determine if EOL experiences in the first spouse are associated with EOL experiences in the second spouse. Design: Nationally-representative, longitudinal survey. Setting: Health and Retirement Study, Wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Research is needed to address these disparities within noncancer populations. Given past concerns that hospice may be underutilized by individuals without a partner, it is promising that we found widowed persons were more likely to enroll in hospice relative to married individuals. The death of a partner may give individuals an opportunity to witness the burdens of disease‐modifying treatments or the benefits of hospice.…”
Section: Discussionmentioning
confidence: 89%
“…Research is needed to address these disparities within noncancer populations. Given past concerns that hospice may be underutilized by individuals without a partner, it is promising that we found widowed persons were more likely to enroll in hospice relative to married individuals. The death of a partner may give individuals an opportunity to witness the burdens of disease‐modifying treatments or the benefits of hospice.…”
Section: Discussionmentioning
confidence: 89%
“…Widowhood : We defined widowhood as a new report of a spouse's death (not gender‐specific) based on self or proxy response in the biennial HRS interview, which also includes the date of the spouse's death. This approach has been used previously with HRS data 33 …”
Section: Methodsmentioning
confidence: 99%
“…34 This algorithm uses cognitive and functional data from the HRS interviews to estimate a predicted probability that the participant has dementia at the time of each biennial interview. 52) 39 (17) 2723 (59) 75-84 210 (33) 3337 (36) 142 (49) 1793 (34) 85+ 311 (54) 978 (12) 92 (35) 307 (7) Female, n (%) 381 (67) 5026 ( 57) 113 (39) 2177 (44) Race and ethnicity, n Non-Hispanic black 129 (14) 1103 ( 8) 29 (7) 416 (5) Hispanic-non-Hispanic other 94 (17) 861 ( 8) 39 ( 16) 434 (7) Less than high school education, n (%) 275 (44) 2308 (23) 98 (35) 961 ( 17 Lives alone (or with spouse only in married-partnered subset) 166 (34) 2509 (32) 196 ( 74) 3940 (84) Medicare Part C enrollee, n (%) 180 (29) 2784 (31) 85 (32) 1487 (31) Medicaid dual eligible, n (%) 174 (28) 990 (10) 64 ( 14 We classified participants with a predicted probability of 0.5 or greater as having dementia based on prior studies. 35 The distribution of dementia probabilities in our sample demonstrated that vast majority of people had probabilities of <0.3 or equal to 1, further justifying this approach.…”
Section: Primary Predictormentioning
confidence: 99%
“…Due to unmeasured items, it is impossible to compare the backgrounds of all respondents and nonresponding survivors; consequently, there may have been considerable selection bias. [47][48][49] This will be assessed further with more relevant items in future studies.…”
Section: Limitationsmentioning
confidence: 99%